Anti-M3 muscarinic acetylcholine receptor antibodies in systemic lupus erythematosus - Reina, Silvia Lorena (2015)
Background: Evidences have shown that anti-M3 muscarinic acetylcholine receptor IgG (anti-M3 mAChR IgG) are clinically useful autoantibody that exert a cholinergic pharmacologic effect binding and interacting with M3 mAChR at the level of exocrine gland (salivary and ocular). Aims: The aim of this study was to determine the associations between serum level of anti-M3 mAChR IgG in patients with systemic lupus erythematosus (SLE) and other autoantibodies, serum prostaglandin E2 (PGE2), and clinical manifestations. Methods: Serum autoantibodies against M3 mAChR synthetic peptide were measured by enzyme-linked immuno absorbent assay (ELISA) using, as an antigen, a 25-mer peptide K-R-T-V-P-D-N-Q-C-F-I-Q-F-L-S-N-P-A-V-T-F-G-T-A-I corresponding to the amino acid sequence of the second extracellular loop of the human M3 mAChR. Serum levels of antinuclear antibodies (ANA), anti-Smith (Sm) antibodies, anti-phospholipid (APL) antibodies, and PGE2 were determined by ELISA in patients with SLE. Results: We found significantly enhanced titers of anti-M3 mAChR IgG in sera from SLE patients compared with healthy individuals (control). In addition, serum levels of PGE2 were significantly higher in SLE patients than in control patients and were significantly higher in active than in non-active SLE. No correlation was found with other autoantibodies present in SLE. By contrast, a positive correlation was found between anti-M3 mAChR IgG and PGE2 serum levels in SLE. Conclusions: As anti-M3 mAChR antibodies present in the sera of SLE patients may be another factor in the pathogenesis of this disease, and the increment of PGE2 in the sera of SLE has a modulatory action on the inflammatory process, suggesting that the presence of these autoantibodies against M3 mAChR may contribute to sustained immune deregulation and the strong inflammatory component observed in SLE.